Oedipus Complex in Traditional China: A Comparative Study towards Myths and Kinship - Gao Han (Traditions and Cultural Heritage: Genesis, Reproduction, and Preservation, 2023)
This article gives a general introduction towards the paradigm of psycho-analysis dealing with Oedipus complex, which thereafter was challenged for its western-centered prejudices by anthropologists with their observations in remote Archipelago societies. Among these, Malinowski’s study about the nuclear complex in Trobriand Islands is the pioneering work. This article follows the conclusion given in the Malinowski’s masterpiece, Sex and Repression in Savage Society, that different social environment and patterns of family organization create different forms of nuclear complex. On the one hand, by generalizing the peculiar characteristics of Chinese familial structure and kinship system mainly demonstrated by Fei Xiaotong, this article makes an attempt on a preliminary analysis towards narrative texts of folklores collected from Chinese Han society to see if there exists the same Oedipus complex with its repression in kinship and expression in myths or not. This article is, on the other hand, a comparative study about forms of patriarchal family between Chinese Han and Western society, aiming at extending the comparative framework between savage society and western modern society, as Malinowski has set up, to an eastern imperial society, China.